APPLICATION OF CO2 LASER PHOTOACOUSTIC SPECTROSCOPY FOR ETHYLENE (C2 H4) GAS DETECTION IN SOIL DURING THE RAINY SEASON - Bergitta Dwi Annawati (Widya Mandala Surabaya Catholic University, 2019)
The photoacoustic spectrometer technique has become the standard in measuring trace samples with the advantages of high sensitivity (up to ppt order), on-line, real time detection and range of operations that are close to 10 8 order. This article reports an experiment using CO2 laser photoacoustic spectroscopy for ethylene (C2 H4) gas detection in the soil during the rainy season based on variations in depth and sampling location using a CO2 laser extracted spectrometer. The lowest limit of detection value (LOD) was obtained at (416 ± 104) ppt. The concentration of ethylene gas in the soil during the rainy season based on the variations in soil depth were (0.18 ± 0.04) ppm for a depth of 0 cm (ground level), (0.17 ± 0.04) ppm for a depth of 15 cm from the ground, and (0.15 ± 0.03) ppm for the depth of 30 cm from the ground. Based on the variations of location of soil, the obtained values were (0.19 ± 0.04) ppm, (0.18 ± 0.04) ppm, and (0.15 ± 0.03) ppm respectively for locations in the North, Center and South were taken around the Biology forest of Gadjah Mada University, which is situated in the western part of the Faculty of Biology and northern section of the Faculty of Mathematics and Natural Sciences. It was concluded that the concentration of ethylene gas in the soil during the rainy season was not significantly affected by depth and location factors.